Effect of flow structures on heat transfer in single and multiphase jet reactors - Deshpande, Sagar S.; Mathpati, Channamallikarjun S.; Gulawani, Sagar S.; Joshi, Jyeshtharaj B.; Kumar, V. Ravi (Industrial & Engineering Chemistry Research, 2009)
High frequency experimental measurements by hot film anemometry (HFA) of liquid velocities and temperature in the region of vapor-liquid (VL) and solid-liquid (SL) interfaces for two important reactor types, namely, condensation jet and jet loop reactors, have been studied for their heat transfer characteristics. An algorithm for flow structure identification has been devised from velocity data based oil (i) zero crossings and (ii) continuous wavelet transform. The wavelet transform algorithm is especially found to be useful in accurately estimating both the age and size distributions of eddies near interfaces in a multiscale framework Using these distributions, it is shown that the calculated values of heat transfer coefficients (HTC) at the SL and VL interfaces show remarkable correspondence with the HTC values obtained experimentally from instantaneous temperature measurements. For this purpose, a modified capacitance model has been proposed that takes into account the information about both the age and size distributions. The results obtained by the present methodology show the improvement possible for calculating the HTC at interfaces when compared with the earlier surface renewal models. It may therefore be used to study the interaction between flow dynamics and heat transfer behavior in chemical process equipment